Evaluation of the mother's anxiety and child's fear in two different age groups in the child's first and second dental visit - Daya Srinivasan; D Senthil; A R Senthil Eagappan; P Rajesh; Kirthika S Prakash; G Shanmugavadivel (Wolters Kluwer Medknow Publications, 2022)
The anxiety of the mother influences the child's behaviour in a dental setting. Objectives: The study aimed at evaluating the mother's anxiety and a child's fear of first and second dental visits in two different age groups. Study Design: The cross-sectional study design consisted of a total of 100 mother-child pairs attending Pediatric Dental clinics was included in the study. Group I consisted of 50 mother-child pairs of 6-8 years of age. Group II consisted of another 50 mother-child pairs between 12-15 years of age. Short Form of the Dental Subscale of the Children's Fear Survey Schedule (DFSS-SF) was administered to the child. Corah's Dental anxiety scale was administered to the mother. The Tell-Show-Do (TSD) technique was used in all children before the treatment. Statistical Analysis Used: SPSS software 21 was used for descriptive and inferential statistics. Pearson's correlation coefficient was used for bivariate correlation between variables in the study. Results: The anxiety level of mothers on both appointment days in both age groups was found to be highly significant. The correlation of maternal anxiety to the gender of the child in both groups was found to be highly significant. Conclusion: The fear of dental treatment was commonly found in children irrespective of gender in both age groups. The TSD technique was found to reduce fear in the subsequent appointment.